Candida isolates from pregnant women and their antifungal susceptibility in a Malaysian tertiary-care hospital - Masri, Siti Norbaya; Md Noor, Sabariah; Mat Nor, Lailatul Akmar; Osman, Malina; Rahman, Md Mostafizur (Professional Medical Publications, 2015)
Objective: Pregnant women are susceptible to vaginal colonization and infection by yeast. The purpose of the study was to determine the prevalence of Candida spp in high vaginal swabs of pregnant women and their antifungal susceptibility. Methods: High vaginal swab samples received from Serdang Hospital, Selangor, Malaysia during 2011 initially had microscopic examination, Gram-staining and fungal culture. These were finally confirmed by growth in chromogenic medium (CHROMagarCandida; Difco BBL, USA) and commercial biochemical identification kit (API 20C AUX; bioMérieux, Lyon, France). Antifungal susceptibility was performed by E-test method. Results: Out of 1163 specimens 200 (17.2%) candida spp were confirmed from high vaginal swabs of pregnant women. Candida albicans (83.5%) is the most common species detected followed by Candida glabrata (16%) and Candida famata (0.05%). All C.albicans and C.famata isolates were susceptible to fluconazole while C.glabrata isolates were dose dependent susceptibility. First and second trimester, and diabetes were considered significant factors in patients for the vaginal candidiasis (p < 0.001). Conclusions: In pregnant women, C. albicans was the frequently isolated yeast from high vaginal swabs. Routine screening and treatment are important of pregnant women regardless of symptoms.